Hydraulicians in Europe 1800-2000. a biographical dictionary of leaders in hydraulic engineering and fluid mechanics /: a biographical dictionary of leaders in hydraulic engineering and fluid mechanics. Volume 2 : ([2009]) - Hager, Willi H
No abstract available